- 222

- 0

Could someone please help me, I do not understand how the author of my text book gets from one point to another. Here is the problem worked out, after the problem I will explain which part I don't understand.

[tex]f(x)=x(x-4)^3[/tex]

[tex]f'(x)=x[3(x-4)^2]+(x-4)^3[/tex]

[tex]=(x-4)^2(4x-4)[/tex]

I do not understand how the author gets from here:

[tex]f'(x)=x[3(x-4)^2]+(x-4)^3[/tex]

to here:

[tex]=(x-4)^2(4x-4)[/tex]

[tex]f(x)=x(x-4)^3[/tex]

[tex]f'(x)=x[3(x-4)^2]+(x-4)^3[/tex]

[tex]=(x-4)^2(4x-4)[/tex]

I do not understand how the author gets from here:

[tex]f'(x)=x[3(x-4)^2]+(x-4)^3[/tex]

to here:

[tex]=(x-4)^2(4x-4)[/tex]

Last edited: